PENGENDALIAN MUTU PEMERIKSAAN KOLESTEROL SERUM KONTROL KOMERSIAL BERDASARKAN WAKTU PENUNDAAN - Altian Nandasari, Fizi; Aryani, Titin; Murdiyanto, Joko (Universitas Pahlawan Tuanku Tambusai, 2024)
Each phase in laboratory examination is at risk of contributing errors that can affect the results. Quality control using control materials is useful for ensuring the accuracy of laboratory examination, one of which is cholesterol examination. This study aims to determine results of quality control with control materials that are immediately examined and delayed 7 hours at room temperature (20-25°C) in cholesterol testing. This study used quantitative methods and quasi experimental design. The sample in this study was commercial control serum and used primary data collection techniques with cross sectional approach. Variables in this study are the length of delay as independent variable and cholesterol levels as dependent variable. Kolmogorov-Smirnov normality test and Independent Sample T-Test significance test were used to analyze the data. Quality control analysis was performed using Levey-Jennings chart and Westgard Rules. The difference between 0 and 7 hours cholesterol examination was 0,44% and the significance test result of p = 0,010 showed that there was significant difference between 0 and 7 hours cholesterol examination. The quality control results of 0-hour cholesterol examination followed Wesgard 12S warning rule and control serum that was delayed for 7 hours at room temperature had results that followed Westgard 12S, 22S and 13S rules. There is a significant difference in cholesterol examination with control serum that is examined immediately and delayed for 7 hours, and delay control serum for 7 hours can cause random and systematic errors.